Molecular interactions between photosystem I and ferredoxin: an integrated energy frustration and experimental model. Issue 10 (1st August 2014) - Cashman, Derek J.; Zhu, Tuo; Simmerman, Richard F.; Scott, Cathy; Bruce, Barry D.; Baudry, Jerome
<x xml:space="preserve">Abstract</x> The stromal domain (PsaC, PsaD, and PsaE) of photosystem I (PSI) reduces transiently bound ferredoxin (Fd) or flavodoxin. Experimental structures exist for all of these protein partners individually, but no experimental structure of the PSI/Fd or PSI/flavodoxin complexes is presently available. Molecular models of Fd docked onto the stromal domain of the cyanobacterial PSI site are constructed here utilizing X‐ray and NMR structures of PSI and Fd, respectively. Predictions of potential protein‐protein interaction regions are based on experimental site‐directed mutagenesis and cross‐linking studies to guide rigid body docking calculations of Fd into PSI, complemented by energy landscape theory to bring together regions of high energetic frustration on each of the interacting proteins. The results identify two regions of high localized frustration on the surface of Fd that contain negatively charged Asp and Glu residues. This study predicts that these regions interact predominantly with regions of high localized frustration on the PsaC, PsaD, and PsaE chains of PSI, which include several residues predicted by previous experimental studies. Copyright © 2014 John Wiley & Sons, Ltd.